An Unusual Case of Multiple‐Gunshot Suicide of an Alcohol‐Intoxicated Cancer Sufferer with Prolonged Physical Activity1. Issue 2 (4th March 2013) - Marnerides, Andreas; Zagelidou, Eleni; Leontari, Roumbini
Abstract Multishot firearm suicides are relatively rare and suggest the possibility of homicide. Physical activity following gunshots to the head, the neck, and the thorax does occur, and immediate incapacitation does not occur in every fatal gunshot wound that penetrates the head or perforates the heart. Cancer patients appear to be at increased suicide risk, but alcohol intoxication is less common in such cases. We present—to the best of our knowledge for the first time—a case of a 54‐year old, male, liver cancer sufferer, who under the influence of alcohol, discharged his revolver three times, suffered, among other wounds, a heart‐perforating wound, and died after c. 1.5 h, being able to talk until just before he died. Our case underlines the importance of keeping an open critical mind when dealing with multiple‐gunshot fatalities, especially when posttraumatic physical activity might be crucial in differentiating homicide from suicide.